2021
DOI: 10.4314/jae.v25i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Digitization of agricultural extension system for effective management of emergency in Nigeria

Abstract: This paper presents challenges facing agricultural extension system in Nigeria most especially, during crises and emergencies, which necessitate the adoption of digitizing extension systems as a basis for improving farmers’ access to extension services during emergencies. The emergence of ICTs has given rise to digitization, which is the delivery of agricultural advice via audiovisual messages (video), interactive voice response (IVR) and short message services (SMS) among others. Efforts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…Masalah penyuluh antara lain terkait dengan kelembagaan penyuluhan, ketenagakerjaan penyuluhan, dan penyelenggaraan penyuluhan (Taryoto, 2014). Tiga isu utama meliputi aspek keterbatasan sumber daya manusia (SDM), keterbatasan pelatihan, akses informasi dan teknologi, keuangan, dan akses pasar (Olagunju et al, 2021). Jadi, secara umum masalah yang dihadapi penyuluh pertanian juga harus dihadapi petani.…”
Section: Pendahuluanunclassified

Tantangan Menjadi Penyuluh Kekinian di Era Disrupsi

Partini,
Sri Peni Wastutiningsih,
Novendra Cahyo Nugroho
et al. 2024
Jupe
“…Masalah penyuluh antara lain terkait dengan kelembagaan penyuluhan, ketenagakerjaan penyuluhan, dan penyelenggaraan penyuluhan (Taryoto, 2014). Tiga isu utama meliputi aspek keterbatasan sumber daya manusia (SDM), keterbatasan pelatihan, akses informasi dan teknologi, keuangan, dan akses pasar (Olagunju et al, 2021). Jadi, secara umum masalah yang dihadapi penyuluh pertanian juga harus dihadapi petani.…”
Section: Pendahuluanunclassified

Tantangan Menjadi Penyuluh Kekinian di Era Disrupsi

Partini,
Sri Peni Wastutiningsih,
Novendra Cahyo Nugroho
et al. 2024
Jupe
“…Ahmed et al (2020) and Lencucha et al (2020) identified policy inconsistency in the national agricultural sector as major consideration in digitalization. Other institutional factors include government and extension management support (Olagunju, 2021), availability of training and provision of support (Fabregas et al, 2022) and distance to training centers (Gyata, 2019). These institutional variables can motivate clients to utilize digital technologies.…”
Section: Distribution Of Articles Across Geographical Zonesmentioning
confidence: 99%
“…This can also assist remarkably in reducing production cost and risk as farmers are authorized to make healthy decisions (Pesce et al, 2019;Ibukun et al, 2021). Digitalization of the agricultural sector will essentially assist in bridging knowledge gaps, implying that majority of the farmers can access advisory services irrespective of the insufficient number of extension staff (Olagunju et al, 2021).…”
Section: Effects Of Digitalization On Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, before the COVID-19 crisis, Olagunju et al (2021) observed that agricultural extension services primarily relied on "on-the-field" methods, including activities like demonstration plots, group training, and farm visits. These approaches involved direct face-to-face interactions, as highlighted by Maertens et al (2020).…”
Section: Introductionmentioning
confidence: 99%